CONSTRAINTS ON THE DYNAMICS OF SUBGLACIAL BASALT ERUPTIONS FROM GEOLOGICAL AND GEOCHEMICAL OBSERVATIONS AT KVERKFJöLL, NE-ICELAND - Höskuldsson A.; Sparks R.S.J.; Carroll M.R. (My University, 2006)
The Kverkfjöll area, NE Iceland is characterised by subglacial basalt pillow lavas erupted under thick ice during the last major glaciation in Iceland. The water contents of slightly vesiculated glassy rims of pillows in six localities range from 0.85±0.03 to 1.04±0.03 wt %. The water content measurements allow the ice thickness to be estimated at between 1.2 and 1.6 km, with the range reflecting the uncertainty in the CO2 and water contents of the melt. The upper estimates agree with other observations and models that the ice thickness in the centre of Iceland was 1.5-2.0 km at the time of the last glacial maximum. Many of the pillows in the Kverkfjöll area are characterised by vesiculated cores (40-60% vesicles) surrounded by a thick outer zone of moderately vesicular basalt (15-20% vesicles). The core contains ~1 mm diameter spherical vesicles distributed uniformly. This observation suggests a sudden decompression and vesiculation of the still molten core followed by rapid cooling. The cores are attributed to a jökulhlaup in which melt water created by the eruption is suddenly released reducing the environmental pressure. Mass balance and solubility relationships for water allow a pressure decrease to be calculated from the observed change of vesicularity of between 4.4 and 4.7 MPa depressurization equivalent to a drop in the water level in the range 440-470 m. Consideration of the thickness of solid crust around the molten cores at the time of the jökulhlaup indicates an interval of 1-3 days between pillow emplacement and the jökulhlaup. Upper limits for ice melting rates of order 10-3 m/s are indicated. This interpretation suggests that jökulhlaups can reactivate eruptions. © Springer-Verlag 2005.
Keywords: ICE THICKNESS ESTIMATES; ICELAND; JöKULHLAUPS; PILLOW LAVAS; SUBGLACIAL VOLCANISM